Interplay between integrins and cadherins to control bone differentiation upon BMP-2 stimulation - Valat, Anne; Fourel, Laure; Sales, Adria; Machillot, Paul; Bouin, Anne-Pascale; Fournier, Carole; Bosc, Lauriane; Arboléas, Mélanie; Bourrin-Reynard, Ingrid; Wagoner Johnson, Amy J.; Bruckert, Franz; Albigès-Rizo, Corinne; et al. (Frontiers in Cell and Developmental Biology, 2023)
Upon BMP-2 stimulation, the osteoblastic lineage commitment in C2C12 myoblasts is associated with a microenvironmental change that occurs over several days. Here we addressed the question as to whether BMP-2 could operate a switch in adhesive machinery to adapt to the new microenvironment and to drive bone cell fate need. We used two different presentation modes for BMP-2 either in solution or via a biomimetic film as a matrix-bound manner. Our findings highlight the switch of integrin and cadherin expression during muscle to bone transdifferentiation upon BMP-2 stimulation. This switch occurs no matter the presentation mode, for BMP-2 presented in solution or via the biomimetic film. While C2C12 muscle cells express M-cadherin and Laminin-specific integrins, the BMP-2-induced transdifferentiation into bone cells is associated with an increase in the expression of cadherin-11 and collagen-specific integrins. Biomimetic films presenting matrix-bound BMP-2 enable the revelation of specific roles of the adhesive receptors depending on the transcription factor. While 3 integrin and cadherin-11 work in concert to control early pSMAD1,5,9 signaling, 1 integrin and Cadherin-11 control RunX2, ALP activity and fibronectin organization around the cells. In contrast, while1 integrin is also important for osterix transcriptional activity, Cadherin-11 and 5 integrin act as negative osterix regulators. In addition, 5 integrin negatively regulates RunX2. Our results show that biomimetic films can be used to delinate the specific events associated with BMP-2-mediated muscle to bone transdifferentiation. Our study reveals how integrins and cadherins work together, while exerting distinct functions to drive osteogenic programming. Different sets of integrins and cadherins have complementary mechanical roles during the time window of this transdifferentiation.